c# pdf reader dll : Delete pages of pdf preview Library control component .net azure winforms mvc solution_manual_of_advanced_engineering_mathematics_by_erwin_kreyszig_9th_edition-14-part240

To help poorer students, we have shifted the derivation of the real form of the solutions
in Case III to the end of the section, but the verification of these real solutions is done
immediately when they are introduced. This will also help to a better understanding.
The student should become  aware  of the  fact that Case III includes  both  undamped
(harmonic) oscillations (if c = 0) and damped oscillations.
Also it should be emphasized that in the transition from the complex to the real form
of the solutions we use the superposition principle.
Furthermore, one should emphasize the general importance of the Euler formula (11),
which we shall use on various occasions.
Comment on How to Avoid Working in Complex
The average engineering student will profit from working a little with complex numbers.
However,  if  one  has reasons  for  avoiding  complex  numbers  here,  one  may apply  the
method of eliminating the first derivative from the equation, that is, substituting y = uv
and determining v so that the equation for u does not contain u
. For v this gives
2v
+av = 0.
A solution is
v= e
ax/2
.
With this v, the equation for u takes the form
u
+(b -
1
_
4
a
2
)u = 0
and can be solved by remembering from calculus that cos
xand sin
xreproduce under
two differentiations, multiplied by -
2
. This gives (9), where
=
b-
1
_
4
a
2
.
Of course, the present approach can be used to handle all three cases. In particular,
u
=0 in Case II gives u = c
1
+c
2
xat once.
SOLUTIONS TO PROBLEM SET 2.2, page 59
2. The standard form is
y
-0.7y
+0.12y = 0.
The characteristic equation
2
-0.7
+0.12 = (
-0.4)(
-0.3) = 0
has the roots 0.4 and 0.3, so that the corresponding general solution is
y
1
=c
1
e
0.4x
+c
2
e
0.3x
.
4. The characteristic equation 
2
+4
π
+4
π
2
=(
+2
π
)
2
=0 has the double root
-2
π
, so that the corresponding general solution is
y= (c
1
+c
2
x)e
2
π
x
.
6. The characteristic equation 
2
+2
+5 = (
+1)
2
+4 = 0 has the roots -1 ± 2i,
so that the general solution is
y= e
x
(A cos 2x + B sin 2x).
8. The characteristic equation is 
2
+2.6
+1.69 = (
+1.3)
2
=0, so that we obtain
the general solution
y= (c
1
+c
2
x)e
1.3x
.
34
Instructor’s Manual
im02.qxd  9/21/05  10:57 AM  Page 34
Delete pages of pdf preview - remove PDF pages in C#.net, ASP.NET, MVC, Ajax, WinForms, WPF
Provides Users with Mature Document Manipulating Function for Deleting PDF Pages
delete pages from a pdf file; acrobat remove pages from pdf
Delete pages of pdf preview - VB.NET PDF Page Delete Library: remove PDF pages in vb.net, ASP.NET, MVC, Ajax, WinForms, WPF
Visual Basic Sample Codes to Delete PDF Document Page in .NET
delete a page from a pdf without acrobat; delete blank page from pdf
10. From the characteristic equation 
2
-2 = (
+√2
)(
-√2
) = 0 we see that the
corresponding general solution is
y= c
1
e
x√2
+c
2
e
x√2
12. The characteristic equation 
2
+2.4
+4 = (
+1.2)
2
+1.6
2
=0 has the roots
-1.2 ± 1.6i. The corresponding general solution is
y= e
1.2x
(A cos 1.6x + B sin 1.6x).
14. The characteristic equation 
2
+
-0.96 = (
-0.6)(
+1.6) = 0 has the roots
0.6 and -1.6 and thus gives the general solution
y= c
1
e
0.6x
+c
2
e
1.6x
.
16. To the given basis there corresponds the characteristic equation
(
-0.5)(
+3.5) =
2
+3
-1.75 = 0.
The corresponding ODE is
y
+3y
-1.75y = 0.
18. The characteristic equation 
(
+3) =
2
+3
=0 gives the ODE y
+3y
=0.
20. We see that the characteristic equation is
(
+1 - i)(
+1 + i) =
2
+2
+2 = 0
and obtain from it the ODE
y
+2y
+2y = 0.
22. From the characteristic equation
2
+2
+1 = (
+1)
2
=0
we obtain the general solution
y= (c
1
+c
2
x)e
x
.
Its derivative is
y
=(c
2
-c
1
-c
2
x)e
x
.
Setting x = 0, we obtain
y(0) = c
1
=4,
y
(0) = c
2
-c
1
=c
2
-4 = -6,
c
2
=-2.
This gives the particular solution
y= (4 - 2x)e
x
.
24. The characteristic equation is
10
2
-50
+65 = 10[
2
-5
+6.5] = 10[(
-2.5)
2
+0.25] = 0.
Hence a general solution is
y= e
2.5x
(A cos 0.5x + B sin 0.5x)
and
y(0) = A = 1.5.
From this we obtain the derivative
y
=e
2.5x
(2.5  1.5 cos 0.5x + 2.5B sin 0.5x - 0.75 sin 0.5x + 0.5B cos 0.5x).
Instructor’s Manual
35
im02.qxd  9/21/05  10:57 AM  Page 35
How to C#: Preview Document Content Using XDoc.Word
How to C#: Preview Document Content Using XDoc.Word. Get Preview From File. You may get document preview image from an existing Word file in C#.net.
cut pages from pdf reader; delete page from pdf online
How to C#: Preview Document Content Using XDoc.PowerPoint
How to C#: Preview Document Content Using XDoc.PowerPoint. Get Preview From File. You may get document preview image from an existing PowerPoint file in C#.net.
delete pdf pages in preview; cut pages from pdf online
From this and the second initial condition we obtain
y
(0) = 3.75 + 0.5B = 1.5;
hence
B= -4.5.
The answer is
y= e
2.5x
(1.5 cos 0.5x - 4.5 sin 0.5x).
26. Dividing  the  ODE  by  10  to get  the  standard  form,  we  see  that  the  characteristic
equation is
2
+1.8
+0.56 = (
+0.4)(
+1.4) = 0.
Hence a general solution is
y= c
1
e
0.4x
+c
2
e
1.4x
.
Now y(0) = c
1
+c
2
=4 from the first initial condition, and by differentiation and
from the second initial condition,
-0.4c
1
-1.4c
2
=-3.8.
The solution of this system of equations is c
1
=1.8, c
2
=2.2. Hence the initial value
problem has the solution
y= 1.8e
0.4x
+2.2e
1.4x
.
28. The roots of the characteristic equation 
2
-9 = 0 are 3 and -3. Hence a general
solution is
y= c
1
e
3x
+c
2
e
3x
.
Now c
1
+c
2
=-2 from the first initial condition. By differentiation and from the
second initial condition, -3c
1
+3c
2
=-12. The solution of these two equations is
c
1
=1, c
2
=-3. Hence the answer is
y= e
3x
-3e
3x
.
30. The characteristic equation is
2
+2k
+(k
2
+
2
) = (
+k)
2
+
2
=0.
Its roots are -k ± i
. Hence a general solution is
y= e
kx
(A cos
x+ B sin
x).
For x = 0 this gives y(0) = A = 1. With this value of A the derivative is
y
=e
kx
(-k cos
x- Bk sin
x-
sin
x+ B
cos
x).
For x = 0 we obtain from this and the second initial condition
y
(0) = -k + B
=-k;
hence
B= 0.
The answer is
y= e
kx
cos
x.
32. The characteristic equation is 
2
-2
-24 = (
-6)(
+4) = 0. This gives as a
general solution
y= c
1
e
6x
+c
2
e
4x
.
Hence y(0) = c
1
+c
2
= 0, and by differentiation, 6c
1
-4c
2
=y
(0) = 20. The
answer is
y= 2e
6x
-2e
4x
.
36
Instructor’s Manual
im02.qxd  9/21/05  10:57 AM  Page 36
VB.NET PDF File Compress Library: Compress reduce PDF size in vb.
a preview component enables compressing and decompressing in preview in ASP images size reducing can help to reduce PDF file size Delete unimportant contents:
cut pages out of pdf online; add and remove pages from pdf file online
C# WinForms Viewer: Load, View, Convert, Annotate and Edit PDF
Erase PDF images. • Erase PDF pages. Miscellaneous. • Select PDF text on viewer. • Search PDF text in preview. • View PDF outlines. Related Resources.
delete blank pages from pdf file; delete pages from a pdf reader
34. Team Project. (A) We obtain
(
-
1
)(
-
2
) =
2
-(
1
+
2
)
+
1
2
=
2
+a
+b = 0.
Comparison of coefficients gives a = -(
1
+
2
), b =
1
2
.
(B) y
+ay
=0. (i) y = c
1
e
ax
+c
2
e
0x
=c
1
e
ax
+c
2
. (ii) z
+az = 0, where
z= y
, z = ce
ax
and the second term comes in by integration:
y= ∫ z dx = c
1
e
ax
+c
2
.
(D) e
(k+m)x
and e
kx
satisfy y
-(2k + m)y
+k(k + m)y = 0, by the coefficient
formulas in part (A). By the superposition principle, another solution is
.
We now  let m * 0. This becomes 0/0, and by  l’Hôpital’s  rule  (differentiation of
numerator and denominator separately with respect to m, not x!) we obtain
xe
kx
/1 = xe
kx
.
The ODE becomes y
-2ky
+k
2
y= 0. The characteristic equation is
2
-2k
+k
2
=(
-k)
2
=0
and has a double root. Since a = -2k, we get k = -a/2, as expected.
SECTION 2.3. Differential Operators. Optional, page 59
Purpose. To  take  a short  look  at the  operational  calculus  of  second-order  differential
operators with constant coefficients, which parallels and confirms our discussion of ODEs
with constant coefficients.
SOLUTIONS TO PROBLEM SET 2.3, page 61
2. (8D
2
+2D - I)(cosh
1
_
2
x) = 8 
1
_
4
cosh
1
_
2
x+ 2 
1
_
2
sinh
1
_
2
x- cosh
1
_
2
x= e
x/2
. The same
result is obtained for sinh
1
_
2
x. By addition of these two results we obtain the result
2e
x/2
for e
x/2
.
4. (D + 5I)(D - I) = (D - I)(D + 5I), and
(D - I)(D + 5I)(e
5x
sin x) = (D - I)(-5e
5x
sin x + e
5x
cos x + 5e
5x
sin x)
=(D - I)(e
5x
cos x)
=-6e
5x
cos x - e
5x
sin x.
For the second given function the answer is 40e
5x
and for the third it is
-5x
2
+8x + 2.
6. (D - 3.7I)(D - 1.8I), y = c
1
e
3.7x
+c
2
e
1.8x
8. (D - 0.7I)(D + 0.7I), y = c
1
e
0.7x
+c
2
e
0.7x
10. (D + (0.1 + 0.4i)I)(D + (0.1 - 0.4i)I), y = e
0.1x
(A cos 0.4x + B sin 0.4x)
12. 4(D +
1
_
2
π
I)
2
, y = (c
1
+c
2
x)e
π
x/2
14. y is a solution, as follows from the superposition principle in Sec. 2.1 because the
ODE is homogeneous linear. In the application of l’Hôpital’s rule, y is regarded as a
function  of 
μ
 the  variable  that  is  approaching  the  limit,  whereas 
is  fixed.
e
(k+m)x
-e
kx

m
Instructor’s Manual
37
im02.qxd  9/21/05  10:57 AM  Page 37
C# PDF Page Insert Library: insert pages into PDF file in C#.net
document files by C# code, how to rotate PDF document page, how to delete PDF page using C# .NET, how to reorganize PDF document pages and how
delete page from pdf acrobat; delete pages of pdf
How to C#: Preview Document Content Using XDoc.excel
How to C#: Preview Document Content Using XDoc.Excel. Get Preview From File. You may get document preview image from an existing Excel file in C#.net.
delete pages from pdf online; delete page pdf acrobat reader
Accordingly, differentiation of the numerator with respect to 
μ
gives xe
μ
x
-0, and
differentiation of the denominator gives 1. The limit of this is xe
x
.
16. The two  conditions follow  trivially from the condition  in the  text. Conversely,  by
combining the two conditions we have
L(cy + kw) = L(cy) + L(kw) = cLy + kLw.
SECTION 2.4. Modeling: Free Oscillations (Mass–Spring System), page 61
Purpose. To present a main application of second-order constant-coefficient ODEs
my
+cy
+ky = 0
resulting as models of motions of a mass m on an elastic spring of modulus k (> 0) under
linear damping c ( 0) by applying Newton’s second law and Hooke’s law. These are
free motions (no driving force). Forced motions follow in Sec. 2.8.
This system should be regarded as a basic building block of more complicated systems,
a prototype of a vibrating system that shows the essential features of more sophisticated
systems as they occur in various forms and for various purposes in engineering.
The  quantitative  agreement  between  experiments  of  the  physical  system  and  its
mathematical  model  is  surprising.  Indeed,  the  student  should  not  miss  performing
experiments if there is an opportunity, as I had as a student of Prof. Blaess, the inventor
of a (now obscure) graphical method for solving ODEs.
Main Content, Important Concepts
Restoring force ky, damping force cy
, force of inertia my
No damping, harmonic oscillations (4), natural frequency 
0
/(2
π
)
Overdamping, critical damping, nonoscillatory motions (7), (8)
Underdamping, damped oscillations (10)
SOLUTIONS TO PROBLEM SET 2.4, page 68
2. (i) √k
1
/m
/(2
π
) = 3/(2
π
), (ii) 5/(2
π
)
(iii) Let K denote the modulus of the springs in parallel. Let F be some force that
stretches the combination of springs by an amount s
0
. Then F = Ks
0
. Let k
1
s
0
=F
1
,
k
2
s
0
=F
2
. Then
F= F
1
+F
2
=(k
1
+k
2
)s
0
.
By comparison, K = k
1
+k
2
=102 [nt/m], √K/m
/(2
π
) = √34/(2
π
) = 5.83/(2
π
).
(iv) Let F = k
1
s
1
, F = k
2
s
2
. Then if we attach the springs in series, the extensions
s
1
and  s
2
under  F add,  so  that  F = k(s
1
+ s
2
),  where  k is  the  modulus  of  the
combination. Substitution of s
1
and s
2
from the other two equations gives
F= k(F/k
1
+F/k
2
).
Division by kF gives
1/k = 1/k
1
+1/k
2
,
k= k
1
k
2
/(k
1
+k
2
) = 19.85.
Hence the frequency is
ƒ = √k/m
/(2
π
) = √6.62
/(2
π
) = 2.57/(2
π
).
38
Instructor’s Manual
im02.qxd  9/21/05  10:57 AM  Page 38
VB.NET PDF delete text library: delete, remove text from PDF file
Visual Studio .NET application. Delete text from PDF file in preview without adobe PDF reader component installed. Able to pull text
delete page in pdf online; delete page on pdf reader
C# Word - Delete Word Document Page in C#.NET
doc.Save(outPutFilePath); Delete Consecutive Pages from Word in C#. int[] detelePageindexes = new int[] { 1, 3, 5, 7, 9 }; // Delete pages.
delete pages out of a pdf file; delete pages in pdf online
4. mg = ks
0
by Hooke’s law. Hence k = mg/s
0
, and
ƒ = (1/2
π
)√k/m
=(1/2
π
)√mg/s
0
m
=(1/2
π
)√g/s
0
=(1/2
π
)√9.80/0
.1
.
The  numeric  value  of  the  last  expression  is  1.58  sec
1
 approximately;  here, 
s
0
=10 cm = 0.1 m is given.
6. my
=-
π
0.3
2
y
γ
, where 
π
0.3
2
yis the volume of water displaced when the buoy
is depressed y meters from its equilibrium position, and 
γ
=9800 nt is the weight of
water per cubic meter. Thus y
+
0
2
y= 0, where 
0
2
=
π
0.3
2
γ
/m and the period
is 2
π
/
0
=2; hence
m=
π
0.3
2
γ
/
0
2
=0.3
2
γ
/
π
=281
W= mg = 281  9.80 = 2754 [nt] (about 620 lb).
8. Team Project. (a) W = ks
0
=25, s
0
=2, m = W/g, and
0
=√k/m
=√(W/s
0
)
/(W/g)
=√980/2
=22.14.
This gives the general solution
y= A cos 22.14t + B sin 22.14t.
Now y(0) = A = 0, y
=22.14B cos 22.14t, y
(0) = 22.14B = 15, B = 0.6775.
Hence the particular solution satisfying the given initial conditions is
y= 0.6775 sin 22.14t [cm].
(b)
0
=√K/I
0
=√17.64
=4.2 sec
1
. Hence a general solution is
θ
=A cos 4.2t + B sin 4.2t.
The derivative is
θ
=-4.2A sin 4.2t + 4.2B cos 4.2t.
The initial conditions give 
θ
(0) = A =
π
/4 = 0.7854 rad (45°) and
θ
(0) = π/12 = 0.2618 rad sec
1
(15°sec
1
), hence B = 0.2618/4.2 = 0.0623.
The answer is
θ
=0.7854 cos 4.2t + 0.0623 sin 4.2t.
(c) The force of inertia in Newton’s second law is my
, where m = 5 kg is the mass
of the water. The dark blue portion of the water in Fig. 45, a column of height 2y, 
is  the  portion  that  causes  the  restoring  force  of  the  vibration.  Its  volume  is 
π
0.02
2
2y. Hence its weight is 
π
0.02
2
2y
γ
, where 
γ
=9800 nt is the weight of
water per cubic meter. This gives the ODE
y
+
0
2
y= 0
where
0
2
=
=0.000 5027
γ
=4.926
and 
0
=2.219. Hence the corresponding general solution is
y= A cos 2.219t + B sin 2.219t.
The  frequency  is 
0
/(2
π
 = 0.353  [sec
1
],  so  that  the  water  makes  about 
20 oscillations per minute, or one cycle in about 3 sec.
π
0.02
2
2 
γ

5
Instructor’s Manual
39
im02.qxd  9/21/05  10:57 AM  Page 39
C# PDF delete text Library: delete, remove text from PDF file in
Delete text from PDF file in preview without adobe PDF reader component installed in ASP.NET. C#.NET PDF: Delete Text from Consecutive PDF Pages.
delete pdf pages reader; copy pages from pdf to another pdf
C# PowerPoint - Delete PowerPoint Document Page in C#.NET
doc.Save(outPutFilePath); Delete Consecutive Pages from PowerPoint in C#. int[] detelePageindexes = new int[] { 1, 3, 5, 7, 9 }; // Delete pages.
delete page from pdf acrobat; delete page on pdf file
10. y
=e
2t
(-2 cos t - sin t) = 0, tan t = -2, t = 2.0344 + n
π
, n = 0, 1, • • •.
12. If an extremum is at t
0
, the next one is at t
1
=t
0
+
π
/
*, by Prob. 11. Since the
cosine and sine in (10) have period 2
π
/
*, the amplitude ratio is
exp(-
α
t
0
)/exp(-
α
t
1
) = exp(-
α
(t
0
-t
1
)) = exp(
απ
/
*).
The  natural  logarithm  is 
απ
/
*,  and  maxima  alternate  with  minima.  Hence 
∆= 2
πα
/
* follows.
For the ODE, ∆ = 2
π
1/(
1
_
2
4 5 -
2
2
) =
π
.
14. 2
π
/
* = 2 sec; 
* =
π
. The time for 15 cycles is t = 30 sec. The quotient of the
corresponding amplitudes at t
0
and t
0
+30 is
e
α
(t
0
+30)
/e
α
t
0
=e
α
30
=0.25.
Thus e
30
α
=4, 
α
=(ln 4)/30 = 0.0462. Now 
α
=c/(2m) = c/4; hence
c= 4
α
=0.1848.
To check this, use 
*
2
4m
2
=4mk - c
2
by (9) which gives
k=
(4m
2
*
2
+c
2
) =
(4m
2
π
2
+c
2
) = 19.74,
and solve 2y
+0.1848y
+19.74y = 0 to get
y= e
0.0462t
(A cos 3.14t + B sin 3.14t)
and
e
0.0462  30
=
1
_
4
.
16. y = c
1
e
(
α
β
)t
+c
2
e
(
α
+
β
)t
, y(0) = c
1
+c
2
=y
0
. By differenting and setting t = 0
it follows that
y
(0) = (-
α
+
β
)c
1
+(-
α
-
β
)c
2
=v
0
.
From the first equation, c
2
=y
0
-c
1
. By substitution and simplification,
(-
α
+
β
)c
1
+(-
α
-
β
)(y
0
-c
1
) = v
0
c
1
(-
α
+
β
+
α
+
β
) = v
0
+(
α
+
β
)y
0
.
This yields the answer
c
1
=[(
α
+
β
)y
0
+v
0
]/(2
β
),
c
2
=[(
β
-
α
)y
0
-v
0
]/(2
β
).
18. CAS Project. (a) The three cases appear, along with their typical solution curves,
regardless of the numeric values of k/m, y(0), etc.
(b) The first step is to see that Case II corresponds to c = 2. Then we can choose
other values of c by experimentation. In Fig. 46 the values of c (omitted on purpose;
the student should choose!) are 0 and 0.1 for the oscillating curves, 1, 1.5, 2, 3 for
the others (from below to above).
(c) This  addresses a  general  issue  arising  in  various  problems  involving heating,
cooling, mixing, electrical vibrations, and the like. One is generally surprised how
quickly certain states are reached whereas the theoretical time is infinite.
(d) General solution y(t) = e
ct/2
(A cos
*t + B sin
*t), where 
* =
1
_
2
4 - c
2
.
The first initial condition y(0) = 1 gives A = 1. For the second initial condition we
need the derivative (we can set A = 1)
y
(t) = e
ct/2
(-
cos
*t -
Bsin
*t -
* sin
*t +
*B cos
*t) .
c
2
c
2
1
4m
1
4m
40
Instructor’s Manual
im02.qxd  9/21/05  10:57 AM  Page 40
From this we obtain y
(0) = -c/2 +
*B = 0, B = c/(2
*) = c/
4 - c
2
. Hence
the particular solution (with c still arbitrary, 0 < c < 2) is
y(t) = e
ct/2
(cos
*t +
sin
*t) .
Its derivative is, since the cosine terms drop out,
y
(t) = e
ct/2
(-sin
*t) (
+
4 - c
2
)
=
e
ct/2
sin
*t.
The  tangent  of  the  y-curve is  horizontal  when y
= 0,  for  the  first positive time
when 
*t =
π
; thus  t = t
2
=
π
/
*  = 2
π
/
4- c
2
.  Now the y-curve oscillates
between  ±e
ct/2
 and  (11)  is  satisfied  if  e
ct/2
does  not  exceed  0.001.  Thus 
ct = 2 ln 1000, and t = t
2
gives the best c satisfying (11). Hence
c= (2 ln 1000)/t
2
,
c
2
=
(4 - c
2
).
The solution of this is c = 1.821, approximately. For this c we get by substitution
* = 0.4141, t
2
=7.587, and the particular solution
y(t) = e
0.9103t
(cos 0.4141t + 2.199 sin 0.4141t).
The graph shows a positive maximum near 15, a negative minimum near 23, a positive
maximum near 30, and another negative minimum at 38.
(e) The main difference is that Case II gives
y= (1 - t)e
t
which is negative for t >1. The experiments with the curves are as before in this project.
SECTION 2.5. Euler–Cauchy Equations, page 69
Purpose. Algebraic  solution  of  the  Euler–Cauchy  equation,  which  appears  in  certain
applications (see our Example 4) and which we shall need again in Sec. 5.4 as the simplest
equation to which the Frobenius method applies. We have three cases; this is similar to
the situation for constant-coefficient equations, to which the Euler–Cauchy equation can
be  transformed  (Team  Project  16);  however,  this  fact  is  of  theoretical  rather  than  of
practical interest.
Comment on Footnote 4
Euler worked in St. Petersburg 1727–1741 and 1766–1783 and in Berlin 1741–1766. He
investigated Euler’s constant (Sec. 5.6) first in 1734, used Euler’s formula (Secs. 2.2, 13.5,
13.6) beginning in 1740, introduced integrating factors (Sec. 1.4) in 1764, and  studied
conformal mappings (Chap. 17) starting in 1770. His main influence on the development
of mathematics and mathematical physics resulted from his textbooks, in particular from
his famous Introductio in analysin infinitorum (1748), in which he also introduced many
of the modern notations (for trigonometric functions, etc.). Euler was the central figure
of the mathematical activity of the 18th century. His Collected Works are still incomplete,
although some seventy volumes have already been published.
(ln 1000)
2

π
2
-2

4 - c
2
1
2
c
2

2
4 - c
2
c

4 - c
2
Instructor’s Manual
41
im02.qxd  9/21/05  10:57 AM  Page 41
Cauchy worked in Paris, except during 1830–1838, when he was in Turin and Prague.
In his two fundamental works, Cours d’Analyse (1821) and Résumé des leçons données
à l’École royale polytechnique (vol. 1, 1823), he introduced more rigorous methods in
calculus, based on an exactly defined limit concept; this also includes his convergence
principle  (Sec. 15.1).  Cauchy  also  was  the first to  give existence proofs  in ODEs.  He
initiated complex analysis; we discuss his main contributions to this field in Secs. 13.4,
14.2-14.4, and 15.2. His famous integral theorem (Sec. 14.2) was published in 1825 and
his paper on complex power series and their radius of convergence (Sec. 15.2), in 1831.
SOLUTIONS TO PROBLEM SET 2.5, page 72
2. 4m(m - 1) + 4m - 1 = 4(m -
1
_
2
)(m +
1
_
2
) = 0, c
1
√x
+c
2
/√x
4. (c
1
+c
2
ln x)/x
6. 2[m(m - 1) + 2m + 2.5] = 2(m
2
+m + 2.5) = 2
[
(m +
1
_
2
)
2
+1.5
2
]
=0. The roots
are -0.5 ± 1.5i. Hence the corresponding real general solution is
y= x
0.5
[
Acos (1.5 ln x) + B sin (1.5 ln x)
]
.
8. 4(m(m - 1) +
1
_
4
)  = 4(m -
1
_
2
)
2
=0 has the double root  m =
1
_
2
; hence  a general
solution is
y= (c
1
+c
2
ln x)√x
.
10. 10m(m - 1) + 6m + 0.5 = 10[m(m - 1) + 0.6m + 0.05] = 10
[
m
2
-0.4m + 0.05
]
=10
[
(m - 0.2)
2
+0.1
2
]
=0. Hence a real general solution is
y= x
0.2
[A cos (0.1 ln x) + B sin (0.1 ln x)].
12. The auxiliary equation is
m(m - 1) + 3m + 1 = m
2
+2m + 1 = (m + 1)
2
=0.
It has the double root -1. Hence a general solution is
y= (c
1
+c
2
ln x)/x.
The first initial condition gives y(1) = c
1
=4. The derivative of y is
y
=c
2
/x
2
+(c
1
+c
2
ln x)/(-x
2
).
Hence the second initial condition gives y
(1) = c
2
-c
1
=-2. Thus c
2
=2. This
gives the particular solution
y= (4 + 2 ln x)/x.
Make sure  to explain to  the  student why  we  cannot  prescribe initial  conditions at 
t= 0, where the  coefficients of the ODE  written  in standard form (divide by x
2
)
become infinite.
14. The auxiliary equation is
m(m - 1) - 2m + 2.25 = m
2
-3m + 2.25 = (m - 1.5)
2
=0,
so that a general solution is
y= (c
1
+c
2
ln x)x
1.5
.
The first initial condition gives y(1) = c
1
=2.2. The derivative is
y
=(c
2
/x)x
1.5
+1.5(c
1
+c
2
ln x)x
0.5
.
42
Instructor’s Manual
im02.qxd  9/21/05  10:57 AM  Page 42
From this and the second initial condition we obtain
y
(1) = c
2
+1.5c
1
=2.5;
hence
c
2
=2.5 - 1.5c
1
=-0.8.
16. Team Project. (A) The student should realize that the present steps are the same as
in the general derivation of the method in Sec. 2.1. An advantage of such specific
derivations  may  be  that  the  student  gets  a  somewhat  better  understanding  of  the
method  and  feels more comfortable with  it.  Of  course, once a  general formula is
available, there  is no  objection to applying  it  to specific  cases,  but often a  direct
derivation may be simpler. In that respect the present situation resembles, for instance,
that of the integral solution formula for first-order linear ODEs in Sec. 1.5.
(B) The Euler–Cauchy equation to start from is
x
2
y
+(1 - 2m - s)xy
+m(m + s)y = 0
where m = (1 - a)/2, the exponent of the one solution we first have in the critical
case. For s * 0 the ODE becomes
x
2
y
+(1 - 2m)xy
+m
2
y= 0.
Here 1 - 2m= 1 -(1 - a) = a, and m
2
=(1 - a)
2
/4, so that this is the Euler–Cauchy
equation in the critical case. Now the ODE is homogeneous and linear; hence another
solution is
Y= (x
m+s
-x
m
)/s.
L’Hôpital’s rule, applied to Y as a function of s (not x, because the limit process is
with respect to s, not x), gives
(x
m+s
ln x)/1 * x
m
ln x
as s * 0.
This is the expected result.
(C) This  is  less  work  than  perhaps  expected,  an  exercise  in  the  technique  of
differentiation  (also  necessary  in  other  cases).  We  have  y = x
m
ln x,  and  with 
(ln x)
=1/x we get
y
=mx
m1
ln x + x
m1
y
=m(m - 1)x
m2
ln x + mx
m2
+(m - 1)x
m2
.
Since x
m
=x
(1a)/2
is a solution, in the substitution into the ODE the ln-terms drop
out. Two terms from y
and one from y
remain and give
x
2
(mx
m2
+(m - 1)x
m2
) + ax
m
=x
m
(2m - 1 + a) = 0
because 2m = 1 - a.
(D) t = ln x, dt/dx = 1/x, y
=y
.
t
=y
.
/x, where the dot denotes the derivative with
respect to t. By another differentiation,
y
=(y
.
/x)
=y
¨
/x
2
+y
.
/(-x
2
).
Substitution of y
and y
into (1) gives the constant-coefficient ODE
y
¨
-y
.
+ay
.
+by = y
¨
+(a - 1)y
.
+by = 0.
Instructor’s Manual
43
im02.qxd  9/21/05  10:57 AM  Page 43
Documents you may be interested
Documents you may be interested